El reproche y el silencio vistos a la luz de la teoría de la cortesía : análisis pragmalingüístico de amor contra un hombre sentado de Gabriel García Márquez (2011)
ABSTRACT: This article presents the results of a pragmalinguistic analysis (specifically those related to politeness theory and conversation analysis) of Gabriel García Márquez´s Diatribe of Love against a Seated Man. The analysis focuses on the reproach and silence used by protagonists Graciela and her husband as their central mode of interaction. Many examples of these communicative acts were selected. For examples of reproach, the face-threatening level was established, also distinguishing when it points to the positive face or the negative one; for silence, refusal to comply with the Transition Relevance Place (TRP) and Moves were established. Some conclusions are that reproach works as a speech act that threatens against both images simultaneously; on the other hand, the husband's silence is communicatively characterized, identifying its meaning despite its devoid of propositional content.